2016
DOI: 10.3390/dj4030026
|View full text |Cite
|
Sign up to set email alerts
|

Final-Year Dental Undergraduate Attitudes towards Specialisation

Abstract: The aim of this study was to explore the attitudes towards postgraduate specialisation of final-year students at one UK dental school and to identify any possible influencing factors. A cross-sectional survey of all 73 final-year students using an anonymous self-report questionnaire was carried out. The response rate was 79%, of which nearly two-thirds were female. Age, ethnicity and parental occupation did not have an effect on the intention to specialise, although student gender did, with more females not wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
29
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 21 publications
5
29
6
Order By: Relevance
“…In this study, several students (81%) responded that they had the desire to pursue a specialist career. This result was highly different compared to other findings (James, Veselina, & Alisa, 2016) where only 38% of students responded to pursue a specialist career. In another hand, the present result was also consistent with other reports (Puryer & Patel, 2016) regarding the desire to pursue a specialization career in dentistry (71%), and the less encouragement by the dental educational institution (James, Veselina, & Alisa, 2016) in the UK within 13% and 18% respectively.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…In this study, several students (81%) responded that they had the desire to pursue a specialist career. This result was highly different compared to other findings (James, Veselina, & Alisa, 2016) where only 38% of students responded to pursue a specialist career. In another hand, the present result was also consistent with other reports (Puryer & Patel, 2016) regarding the desire to pursue a specialization career in dentistry (71%), and the less encouragement by the dental educational institution (James, Veselina, & Alisa, 2016) in the UK within 13% and 18% respectively.…”
Section: Discussioncontrasting
confidence: 95%
“…This result was highly different compared to other findings (James, Veselina, & Alisa, 2016) where only 38% of students responded to pursue a specialist career. In another hand, the present result was also consistent with other reports (Puryer & Patel, 2016) regarding the desire to pursue a specialization career in dentistry (71%), and the less encouragement by the dental educational institution (James, Veselina, & Alisa, 2016) in the UK within 13% and 18% respectively. Encouragement or orientation of the students in the field of specialization should be one of the preoccupations of the Dental educational institution as was mentioned that (Scarbecz & Ross, 2007) students were six times more likely to specialize if they received encouragement compared to the student who had not.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Due to the unique and valuable learning opportunities these posts offer, and the large amount of interest of pursuing specialty training amongst juniors, the number of dentists undertaking these posts seems likely to increase . It has even been suggested that DFT posts should all be 2 years long, with a mandatory year in an OMFS unit as a DCT .…”
Section: Introductionmentioning
confidence: 99%
“…amongst juniors, the number of dentists undertaking these posts seems likely to increase. 3 It has even been suggested that DFT posts should all be 2 years long, with a mandatory year in an OMFS unit as a DCT. 4 It would therefore be prudent to ascertain whether current OMFS DCT posts allow trainees to gain significant improvement in confidence of minor surgical procedures when compared to GDPs of similar experience.…”
mentioning
confidence: 99%